2017
DOI: 10.1186/s13063-017-2171-5
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture lowering blood pressure for secondary prevention of stroke: a study protocol for a multicenter randomized controlled trial

Abstract: BackgroundStroke is the prime cause of morbidity and mortality in the general population, and hypertension will increase the recurrence and mortality of stroke. We report a protocol of a pragmatic randomized controlled trial (RCT) using blood pressure (BP)-lowering acupuncture add-on treatment to treat patients with hypertension and stroke.MethodsThis is a large-scale, multicenter, subject-, assessor- and analyst-blinded, pragmatic RCT. A total of 480 patients with hypertension and ischemic stroke will be rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Meta-analyses have challenged the efficacy of acupuncture for the treatment of hypertension as a risk factor for stroke (Sibbritt et al, 2018). However, controlling BP via acupuncture as an additive treatment is an effective secondary prevention of stroke (Du et al, 2017). In stroke patients complicated with hypertension, antihypertensive acupuncture improved the National Institutes of Health stroke scale and Barthel index, both of which are indicative of stroke-related neurologic deficit.…”
Section: Effects Of Acupuncture Techniques Aimed At Treating Hypertenmentioning
confidence: 99%
“…Meta-analyses have challenged the efficacy of acupuncture for the treatment of hypertension as a risk factor for stroke (Sibbritt et al, 2018). However, controlling BP via acupuncture as an additive treatment is an effective secondary prevention of stroke (Du et al, 2017). In stroke patients complicated with hypertension, antihypertensive acupuncture improved the National Institutes of Health stroke scale and Barthel index, both of which are indicative of stroke-related neurologic deficit.…”
Section: Effects Of Acupuncture Techniques Aimed At Treating Hypertenmentioning
confidence: 99%
“…Several studies have confirmed the effect of acupuncture interventions on BP control [ 14 , 15 , 16 , 17 , 18 ] and acupuncture was found to lower BP and relieve hypertension symptoms in various cases. Therefore, acupuncture treatment may also be effective in the management of BP in postmenopausal women.…”
Section: Introductionmentioning
confidence: 95%
“… 9 Long-term use of antihypertensive medication may result in side effects and increase the cost of medical care, thereby lowering the quality of life. 10 …”
Section: Introductionmentioning
confidence: 99%
“…In several studies, acupuncture showed a BP-lowering effect in men and women in the prehypertension and hypertension stages. 9 , 10 , 11 , 12 Acupuncture has also been shown to be effective in controlling vasomotor symptoms, such as hot flushes in menopausal women. 13 Recent studies have shown that the use of acupuncture is increasing and it is effective for lowering blood pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation